How to Tell the Story? : On Story and Narrative in the Research Process – A pragmatic constructive approach - Henriksen, Lars Bo (Journal of Pragmatic Constructivism, 2021)
Note: the paper has been updated 24 August 2021. In this paper I investigate the problems of data collection, data analysis and the final communication of the results of our research, when doing social science that we, ourselves, are part of. Central to this are the concepts life world, language games and stories and narratives. How do we collect stories and narratives in the field, how do we construct scientific narratives that are both reliable and valid? And finally, how do we, as researchers present our newly constructed narrative to a – hopefully – interested audience? That is, how do you, as a consumer of scientific narratives, read what I have been writing? Finally, I will discuss the problem of handing over research results to the people that we are doing research with. This is all done within a framework of a pragmatic constructivist paradigm.